Understanding the impact of persistent symptoms in schizophrenia: cross-sectional findings from the Pattern study - Haro, Josep Maria; Zink, Mathias (Schizophrenia research, 2015)
The high societal burden of schizophrenia is largely caused by the persistence of symptoms and accompanying functional impairment. To date, no studies have specifically assessed the course of persistent symptoms or the individual contributions of positive and negative symptoms to patient functioning. The cross-sectional analysis of the Pattern study provides an international perspective of the burden of schizophrenia. Clinically stable outpatients from 140 study centers across eight countries (Argentina, Brazil, Canada, France, Germany, Italy, Spain and the United Kingdom) were assessed using clinical rating scales: Positive and Negative Syndrome Scale (PANSS), Clinical Global Impression-Schizophrenia (CGI-SCH) Scale and the Personal and Social Performance (PSP) Scale. Additional measures included patient-reported outcomes, patient socio-demographic variables, living situation, employment and resource use. Overall, 1379 patients were assessed and analyzed and had similar sociodemographic characteristics across countries, with 61.6% having persistent positive and/or negative symptoms. Positive and negative symptoms had been persistent for a mean of 9.6 and 8.9years (SD: 8.8 and 9.6), respectively. Approximately 86% of patients had a functional disability classified as greater than mild. Patients with a higher PANSS Negative Symptom Factor Score were more likely to have a poorer level of functioning. This analysis examines individual contributions of persistent positive and negative symptoms on patient functioning in different countries. A high prevalence of patients with persistent symptoms and functional impairment was a consistent finding across countries. Longitudinal observations are necessary to assess how to improve persistent symptoms of schizophrenia and overall patient functioning.
Gesehen am 13.09.2017